Review on the Therapeutic Role of Asclepias tuberosa Seeds in Diabetes Management - Shukla, Shivangi; Singh, Prashant; Shukla, Rajeev (Journal of Biomedical and Pharmaceutical Research, 2024)
Diabetes mellitus (DM) presents a significant global health challenge characterized by elevated blood glucose levels, leading to debilitating complications. Despite various therapeutic approaches, effective glucose regulation remains elusive, often accompanied by adverse effects from current medications. Medicinal plants, including Asclepias tuberosa, have shown promise in managing blood glucose levels with fewer side effects. This review highlights the potential of Asclepias tuberosa as herbal antidiabetic agents based on recent literature, suggesting avenues for further research and therapeutic development in DM management. Considering the urgent need for safer and more effective antidiabetic treatments, exploring the therapeutic potential of Asclepias tuberosa presents a promising avenue for addressing this growing public health concern. Future studies should focus on elucidating the mechanisms of action, conducting clinical trials to validate the efficacy and safety of Centaurea-based interventions in DM management, and exploring synergistic effects with existing therapies. Furthermore, within the context of utilizing plant materials for the treatment of Diabetes mellitus, particular attention is directed towards the utilization of Asclepias tuberosa seeds. Asclepias tuberosa, commonly known as butterfly weed or pleurisy root, is a medicinal plant native to North America. Traditionally, various parts of this plant, including the roots, leaves, and seeds, have been used in folk medicine for their purported therapeutic effects Keywords: Diabetes mellitus, Asclepias tuberosa, antidiabetic agents, herbal remedies, blood glucose regulation.